Education, Upbringing, Teacher Competence, Students Independent Education, Motivation Correctness - Rahmatova Zulxumor Mamitxonovna (Genius Journals, 2023)
This article reflects on the role of students in the formation of professional competencies in the training of independent personnel and its organization
Keywords: education; thinking; motivation